Pattern and Characteristic of Sports Related Injury in Emergency Department Sardjito Hospital - Andreas Wahyu Wicaksono (Journal of Global Pharma Technology, 2019)
Objective. Sport activites have been encouraged to everyone due to its benefits to the physical fitness, improving the endurance, and has psychological good impacts. But, sport activites also carries risk of injury to the body. Sports-related injuries are not an uncommon cause of ED visit. The aim of this study was to identify the pattern and characterize emergency department (ED) visits that result from sports-related injuries across the Sardjito Hospital.Methods. The study took place retrospectively observational study over a period of two years from January 2014 to December 2015 and included people 3 years of age or over. Any patient presenting with an injury attributable to participation in organised sport had their details and phone number noted in the medical record form by the orthopaedic resident. The patient medical record were analysed retrospectively. Demographic trends, pattern and characterstic for each patient were recorded.Results. A total of 133 elligible patients were enrolled to this study, 98 were male with the mean of age was 17.5. The most common type of sport that cause of injury was cycling (22.6%), followed by running (21.8%) and then football (17.3%). The majority of the patient sustained upper extremity injury (75.9%). 108 patients sustained fracture, 15 dislocation, and 10 soft tissue injury. There was statistical differences between type of injury as compared with age group (p = 0,000), the age group of <10 years old, 11-20 years old, 31-40 years old and >40 years old suffered more fracture than dislocation and soft tissue injury. There was statistical differences between type of injury as compared with injured extremity (p = 0.03), the injury mostly affected superior extremity, but there was no statistical difference between type of injury as compared with type of sports, gender and side of injury (left or right) (p > 0.05). Conclussions. Sports can cause musculoskeletal injuries, good preparation must be taken to avoid severe injury. High percentage of upper extremity injury and lower extremity injury, the specific type and location of injuries of each sport should be known by health professionals.Keyword: sport injury, emergency department, age group, gender, location and types of injuries